1983
DOI: 10.1159/000128343
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Acute Thrombogenicity of Human Umbilical Veins after Heparin and Alcohol Treatment

Abstract: Nine glutaraldehyde-tanned human umbilical veins (GAUV) were incubated in heparin followed by storage in ethyl alcohol 50% (HAUV). These grafts were compared to five GAUV flushed with a heparinized solution without subsequent treatment in alcohol (HsAUV) and four nonheparinized GAUV (NHUV) placed in the contralateral carotid arteries of dogs for approximately 3 h. The thrombogenicity was evaluated by measuring the platelet adhesion and aggregation (51Cr), fibrinogen accumulation (125I-fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…In our previous study with 51Cr,!abeled platelets in dogs, this treatment was shown to decrease the thrombogenicity, which was also accentuated by alcohol treatment. 6 These results are Confirmed by the present investigation. Moreover, from the radioactivity measurements, the results for the covalently heparinized grafts indicate that this method may also improve the antithrombotic characteristics of human umbilical vein grafts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our previous study with 51Cr,!abeled platelets in dogs, this treatment was shown to decrease the thrombogenicity, which was also accentuated by alcohol treatment. 6 These results are Confirmed by the present investigation. Moreover, from the radioactivity measurements, the results for the covalently heparinized grafts indicate that this method may also improve the antithrombotic characteristics of human umbilical vein grafts.…”
Section: Discussionsupporting
confidence: 90%
“…Despite these problems, SlCr-labeled platelets could be used in a previous study in which the total activities of human umbilical vein grafts were recorded. 6 Since one of the aims of the present study was to evaluate the spatial distribution of platelets along the grafts, the 13-emitting isotope 32p was chosen as being more suitable. Although the efficiency of 32P-platelet labeling is lower than for 51Cr, this is more than compensated for by the ease with which the background radiation from all parts of the body other than that being studied can be removed by simple shielding.…”
Section: Discussionmentioning
confidence: 99%
“…Blood velocity is a key factor in the ap parent thrombogenicity of a surface which, however, can be reduced [30,31]. Synthetic or chemically processed biological vascular prostheses have characteristic thrombotic threshold velocities below which thrombosis occurs [32], It is therefore important to match the diameter of the prosthesis to that of the adjacent blood vessel in order to maintain high blood velocities and avoid turbulence.…”
Section: Discussionmentioning
confidence: 99%
“…Despite much effort, the patency rates of syn thetic grafts smaller than 6 mm in diameter remain disappointing. In the search for im proved grafts, much work has been done on studying and decreasing the thrombogenicity of graft surfaces [Esquivel et al, 1983], Among non-surface factors, the difference in compliance between graft and artery has been 1 Supported by grants from the Swedish Medical Research Council No. 00759 and 7182. the Swedish National Association against Heart and Chest Dis eases and the Tutise Lindgren Foundation.…”
Section: Introductionmentioning
confidence: 99%